FAKTOR-FAKTOR PEMANFAATAN TEKNOLOGI INFORMASI (TI) YANG MEMPENGARUHI NILAI PERUSAHAAN DI ERA INDUSTRI 4.0 - Dewi, R.Rosiyana; Ramadhan, Dwiky Yanuar (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This research was conducted to analyze the influence of IT Governance, IT Investment, and the Use of Big Data Technology on Firm Value in the Digital 4.0 Era in non-financial companies listed on the Indonesia Stock Exchange in the period 2020 to 2022. The population in this study counted 108 non-financial companies listed on the Indonesia Stock Exchange. This research is a quantitative research, namely by collecting data using secondary data. The data in this study were obtained from financial report data on the official website of the Indonesia Stock Exchange (IDX) (www.idx.co.id). The results of this study indicate that IT Governance and IT Investment, have an positive effect on Firm Value. And the use of Big Data technology has no effect on Firm Value.